Reduction of carbon dioxide and organic carbonyls by hydrosilanes catalysed by the perrhenate anion. Issue 13 (8th June 2017) - Morris, Danny S.; Weetman, Catherine; Wennmacher, Julian T. C.; Cokoja, Mirza; Drees, Markus; Kühn, Fritz E.; Love, Jason B.
Abstract : A simple quaternary ammonium perrhenate salt catalyses the hydrosilylation of aldehydes, ketones, and carbon dioxide, and the methylation of amines using carbon dioxide. DFT calculations show that a perrhenate hypervalent silicate interacts directly with CO2 . Abstract : The simple perrhenate salt [N(hexyl)4 ][(ReO4 )] acts as a catalyst for the reduction of organic carbonyls and carbon dioxide by primary and secondary hydrosilanes. In the case of CO2, this results in the formation of methanol equivalents via silylformate and silylacetal intermediates. Furthermore, the addition of alkylamines to the reaction mixture favours catalytic amine N -methylation over methanol production under certain conditions. DFT analysis of the mechanism of CO2 reduction shows that the perrhenate anion activates the silylhydride forming a hypervalent silicate transition state such that the CO2 can directly cleave a Si–H bond.